Implementation of Contextual Teaching & Learning Model in Teaching Procedure Text at VII Grade in SMP PGRI 3 Denpasar - Mirsa Umiyati; Aron Meko Mbete; Asradi Cerman; Rika Purnama Sari (Linguistic Community Services Journal, 2022)
This community services program is entitled â€œImplementation of Contextual Teaching and Learning Model in Teaching Procedure Text at VII Grade in SMP PGRI 3 Denpasarâ€. The partner of this program is SMP PGRI 3 Denpasar. While the object of the programâ€™s implementation is the students of SMP PGRI 3 Denpasar, especially the VII Grade. It takes place at SMP PGRI 3 Denpasar. This community services program aims to increase understanding and ability in in understanding about Contextual Teaching and Learning Models in Teaching Procedure Texts, Increasing competitiveness (increasing the quality, quantity, and added value of goods, services, product diversification, or other resources), Increase the application of science and technology to society This is a very important and useful program to increase the understanding of the the students of SMP PGRI 3 Denpasar, especially the VII Grade so that they can provide explanations related to Contextual Teaching and Learning Models in Teaching Procedure Texts. The targeted output plan related to the implementation of this PKM activity is the form of publication in the Community Service Journal in the form of ISSN articles and books in the form of teaching and learning documentation to student of SMP PGRI 3 denpasar especially VII grade.